Characterization of Cellulose Extracted from Garlic Waste via Alkaline Treatment and Its Effect on Yield - Fahni, Yunita; Atro Auriyani, Wika; Amelia, Devita; Rizki Safitra, Edwin; Riana Saputri, Desi; Damayanti, Damayanti; Sanjaya, Andri; Christian Surya Atmaja, Michael; Nyoman Wiswa Kananda, I; Surya Ningrum, Riska; Mahardika, Melbi (Reaktor, 2025)
Garlic waste—including straws, bulbs, and skins—is an agricultural residue contributing to household waste. Rich in cellulose, garlic waste can be converted into various value-added products through proper processing. In this study, cellulose was extracted from garlic waste using alkaline treatment to investigate the influence of sodium hydroxide (NaOH) concentration on the characteristics of the resulting cellulose. NaOH solutions with varying concentrations of 2%, 7%, 14%, and 20% were used during the alkalization process. FTIR spectra revealed transmittance changes with increasing concentration, indicating a reduction in lignin content. The resulting cellulose exhibited needle-like structures, and garlic fibers with amorphous morphology showed cleaner surfaces at a NaOH concentration of 20%. The highest extract yield from the alkalization process was 62.7%, achieved at a NaOH concentration of 2%. These findings demonstrate the potential of garlic waste as a cellulose source and its applicability for producing derivative products such as thin films, optical fibers, and bioplastic raw materials.